An ecclesiology and an evangelizing option: Commenting on the book "The signal of each moment" - de Prado, Consuelo (1994)
We are facing a publication that must be read together to make us of the practice be read together to take charge of the ecclesial practice that sustains it. The global reading allows us to assess the nuances and emphases of each moment or region. Also, taking note of the particularities, far from moving away from the common thread, helps us discover its cumulative richness.